Pengaruh Pupuk Kandang Ayam dan Jenis Biochar terhadap Pertumbuhan dan Hasil Kubis Bunga (Brassica oleraceae var. Botytis L.) di Tanah Berpasir - Isa Wahyuni; Pienyani Rosawanti; Hariyadi; Muh. Azhari (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
Brassica oleraceae var. Botytis L. is a type of vegetable plant in the cabbage family that originates from Europe. This research aims to test and analyze the response of cauliflower to chicken manure and types of biochar. The study was conducted from October 2024 to January 2025 at the experimental garden and research of Campus III UMPR, Jl. Ir Soekarno No.I, Palangka Raya City, Central Kalimantan. This study used a randomized design consisting of two factors, where the first factor was three levels of chicken manure with three treatment doses of 10, 20, and 30 tons per hectare, while the second treatment was the type of biochar with control, rice husk, and empty palm oil bunches. The research shows that the treatment of chicken manure fertilizer affects the height of plants at 35 DAP, the fresh weight of flowers, and the circumference of flowers. The efficient dose for observations of plant height and fresh weight of flowers is 20 ton/ha, while for flower circumference it is 30 ton/ha. The treatment of biochar type has a significant effect on the observation of the height of plants at 35 DAP.